2019
DOI: 10.3389/fimmu.2019.00903
|View full text |Cite
|
Sign up to set email alerts
|

MAdCAM-1-Mediated Intestinal Lymphocyte Homing Is Critical for the Development of Active Experimental Autoimmune Encephalomyelitis

Abstract: Lymphocyte homing into the intestine is mediated by binding of leukocytes to mucosal addressin cell adhesion molecule 1 (MAdCAM-1), expressed on endothelial cells. Currently, the immune system of the gut is considered a major modulator not only of inflammatory bowel disease, but also of extra-intestinal autoimmune disorders, including multiple sclerosis (MS). Despite intense research in this field, the exact role of the intestine in the pathogenesis of (neuro-)inflammatory disease conditions remains to be clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…ICAM-2 also mediates leukocyte-endothelial adhesion in cerebral vasculature ( 94 ), and neurons upregulate ICAM-2 with the formation of tau NFTs ( 95 ). Tau burden and cerebrovascular pathology also appeared to additively interact with regard to microvascular expression of MAdCAM-1, a leukocyte adhesion molecule that is upregulated in the CNS following chronic vascular inflammation ( 96 98 ). Since MAdCAM-1 detection was variable across samples, future studies in a larger cohort are warranted to clarify the relationship between MAdCAM-1, tau pathology, and cerebrovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-2 also mediates leukocyte-endothelial adhesion in cerebral vasculature ( 94 ), and neurons upregulate ICAM-2 with the formation of tau NFTs ( 95 ). Tau burden and cerebrovascular pathology also appeared to additively interact with regard to microvascular expression of MAdCAM-1, a leukocyte adhesion molecule that is upregulated in the CNS following chronic vascular inflammation ( 96 98 ). Since MAdCAM-1 detection was variable across samples, future studies in a larger cohort are warranted to clarify the relationship between MAdCAM-1, tau pathology, and cerebrovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the findings of the VIOLET trial strongly suggest that Vitamin D supplementation alone has no benefit as an intervention in the critically ill, our inclusion of Vitamin D in COVID-19 treatment, aside from the evidence suggesting the possibility of a more potent therapeutic role in both viral syndromes and COVID-19 (likely few patients with viral syndromes were included in the VIOLET study), is largely based on the therapeutic enhancement of corticosteroid effect when co-administered with Vitamin D, similar to the synergistic effects of corticosteroids with Vitamin C. 155 Investigators have demonstrated that Vitamin D up-regulates glucocorticoid receptors which leads to increased T-cell apoptosis while it can also enhance the corticosteroid effect on and suppression of cytokine production in peripheral blood cell monocytes. 156 -158…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…Although the findings of the VIOLET trial strongly suggest that Vitamin D supplementation alone has no benefit as an intervention in the critically ill, our inclusion of Vitamin D in COVID-19 treatment, aside from the evidence suggesting the possibility of a more potent therapeutic role in both viral syndromes and COVID-19 (likely few patients with viral syndromes were included in the VIOLET study), is largely based on the therapeutic enhancement of corticosteroid effect when co-administered with Vitamin D, similar to the synergistic effects of corticosteroids with Vitamin C. 155 Investigators have demonstrated that Vitamin D up-regulates glucocorticoid receptors which leads to increased T-cell apoptosis while it can also enhance the corticosteroid effect on and suppression of cytokine production in peripheral blood cell monocytes. [156][157][158] Recently, in a pilot RCT of Vitamin D therapy in hospitalized COVID-19 patients using calcifediol, the direct precursor to the active form of Vitamin D in the serum, patients were treated on the day of admission with an oral dose of 0.532 mg (roughly equivalent in potency to a dose of 68,000 IU of Vitamin D 3 ), then they gave half the dose on day 3, day 7, and weekly thereafter. They found that of the 50 patients treated with calcifediol, one required admission to the ICU (2%) while of 26 untreated patients, 13 required admission to the ICU (50%), p < .001, OR 0.02 [0.002-0.17].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Along with its role in the development of intestinal lymphoid tissues. Nkx2-3 is crucial for the expression and regulation of the mucosal addressin cell adhesion molecule-1 (MADCAM-1) on the spleen sinus lining cells and on high endothelial venules of the mesenteric lymph nodes and Peyer’s patches [ 17 , 18 , 19 , 20 ]. Nkx2-3 has an important role in spleen organization and function, since it controls the correct micro-environment for B cell maturation and T-cell-dependent (TD) immune reaction [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%